The Effect of an Interdisciplinary Teaching Approach on Seventh-Grade Pupils’ Motivation in Physical Education Class - Gotzaridis, Χρήστος; Papaioannou, Αθανάσιος; Antoniou, Παναγιώτης; Albanidis, Ευάγγελος (Inquiries in Physical Education and Sport, 2007)
This study was made in order to examine the effect of the interdisciplinary teaching approach, on the motivation of pupils aged 13±1 years old. In this particular study, five (5) interdisciplinary interventions, involving Physics concepts, were planned. The sample involved 487 pupils divided in three groups (one experimental and two control groups). Fourteen (14) Physical Education teachers participated in the study. The result was evaluated considering the following factors. a) Lesson satisfaction b) Goals orientation c) Perceived motivational climate d) Μotivation. The study was held through four questionnaires. The questionnaires were handed out before the intervention and after the 1st, 3rd and 5th sessions. The results revealed a gradual increase in the score of the satisfaction and the intrinsic motivation questionnaires, while was noted a decrease in the score of a-motivation. We are led to the conclusion that the interdisciplinary intervention in the experimental group resulted in, a greater satisfaction among the pupils, an increase of interest for improvement and knowledge (intrinsic motivation).